Web based temperature control-heat bar experiment - Mohd Najmuddin Bin Abdul Razak (2023)
The aim and objective of this project is to allow users to monitor the results of experiment via the Internet from remote places, which will be most beneficial for distance learning process. The particular experiment in this project is the 'heat bar experiment'. This system uses eight thermocouple wires to sense the heat distribution along a heat-conducting bar. The variation of temperature is controlled by a heater, which is connected to a heat bar through a personal computer using a computer programming language called the LabVIEW.